PARTISIPASI MASYARAKAT TERHADAP PENGEMBANGAN OBJEK WISATA DI KECAMATAN KEMA KABUPATEN MINAHASA UTARA - Junus, Alan Yehezkiel Langi; Syafriny, Reny; Egam, Pingkan P (SPASIAL, 2021)
This research focuses on the community around the tourist attraction in Kema District, namely in Kema II Village, Kema III Village, and Makalisung Village. The method approach used is descriptive quantitative analysis, as well as the measuring tool used, namely the application of the SPSS (Statistical Package for the Scientists) version 25 program. The objectives, theories and analysis used are to identify the social characteristics of the community (Slamet, 1993), the forms of community participation (Dusseldorp, 1981), as well as the level of community participation (Sherry Arnstein, 1969), using analysis a frequency distribution. Then the analysis was crosstabs used to compare the number of people's participation in the first and second research objectives. The results of this study indicate that, community participation begins with the social characteristics of the community (gender, age, job level, type of work, and income level). This makes the difference between each individual characteristic that a person has in participating in community participation. Nevertheless, the community still tries and cooperates in carrying out its role in the activities of its forms of participation, without limiting the differences of each person's individual characteristics. The community's activeness in participating in activities shows that the community cares about a series of activities organized by the village government and is willing to be invited to cooperate, in order to improve and develop their village. This can be seen from the fairly good number of community participation, as well as the voluntary involvement of the community. The level of community participation, Kema II and Kema III villages are at thelevel Consultation, Makalisung Village is at thelevel Informing. Keywords: Levels and Forms of Community Participation, Tourism Object Development